Effects of concentrate feeding strategy on the performance of dairy cows housed in a free stall barn - Yrjänen, Satu; Kaustell, Kaisa; Kangasniemi, Reima; Sariola, Juha; Khalili, Hannele (Elsevier, 2003)
An experiment was conducted to compare two concentrate feeding strategies using 63 Finnish Ayrshire dairy cows in a free stall barn during 1 and 26 weeks of lactation. The first strategy consisted of offering concentrates separately four times a day (separate feeding, SF) with a computerised concentrate self feeder whilst in the second strategy concentrates were fed as total mixed ration (TMR). For SF diets grass silage was offered ad libitum and concentrates were offered at 0.33 kg per kg energy corrected milk (ECM) yield. Primiparous cows were given an additional kg per day of concentrate. The TMR based on grass silage and concentrates in the proportions 0.55 and 0.45 on a DM basis, was offered ad libitum. Feeding regimen had no effect (P>0.05) on mean milk production, milk composition, silage or total DM intake, live weight or body condition score. However, there were differences over the lactation curve between the treatment groups as cows fed separately produced more milk in early lactation and cows fed TMR had higher milk yield later in the lactation period. For cows in early and mid lactation there was no benefit in feeding concentrates according to milk yield compared with feeding a fixed proportion of concentrate in the diet.
ent. Kaisa Kaustell nyk. Kaisa Kuoppala
Keywords: Ko; lypsykarja; lehmät; väkirehut; ruokinta; rehunkulutus; maidontuotanto; pihatot; dairy cattle; dairy cows; concentrates; feeding; feed intake; milk production; concentrate feeding; loose housing